The management of household mask wastes during COVID-19 era - Asti Mulasari Surahma; Savitri Sheila (BIO Web of Conferences)
Mask is one of the largest domestic infectious wastes during the pandemic COVID-19. However, some people do not know how to manage their mask waste properly. This study aims to determine the relationship between education, knowledge, attitudes, and community participation in household mask waste management. This study used quantitative analytic research with a Cross-Sectional approach. Furthermore, the sampling method used the total sample. The number of samples were 73 respondents. Questionnaires were distributed as research tools to collect data on education, knowledge, and attitudes towards household waste management participation. data analysis was performed by chi-square analysis using computer analysis software. The study results of 73 respondents indicated that 56.8% had higher education, 79.5% had good knowledge, 79.5% had a positive attitude, and 65.8% had good participation, concecutively. The results of the education bivariate test obtained a p-value of 0,332 (p>0.05), knowledge of p-value 0.003 (p <0.05) RP 2,175 (95% CI: 1,209 - 3,912), and attitude p-value 0.018 (p <0.05) RP 2,578 (95% CI : 1,467 - 4,530). We highlighted that there were relationship between knowledge and attitude with community participation in household waste management. On the contrarty with education and community participation has no relationship in household mask waste management.